Teknologi Live Streaming sebagai Media Penunjang Dakwah dan Kegiatan Belajar Mengajar untuk Mendukung Cyber University - Achmad Teguh Wibowo; Faris Mushlihul Amin (Proceedings of Annual Conference for Muslim Scholars, 2018)
in line with the vision and mission of UIN Sunan Ampel (UINSA) to become a superior, competitive and international campus, one of the biggest challenges faced is the unavailability of da'wah facilities and teaching and learning activities that can reach all targets (community,new students and civitas academic). Available media now such as website and public relations promotion felt less in terms of supporting da'wah and learning activity that happened at UINSA, website which now only promote UINSA and display announcement and agenda what is in UINSA, while promotion of public relations only direct to area most of whose activities are only to attract new students. This research focuses on making live streaming technology as a medium of supporting da'wah and teaching and learning activities at UINSA. Many propaganda that can be broadcasted live at UINSA such as guest lectures and public lectures that should be enjoyed and watched by all the public, and this technology can help students in the field of broadcasting to practice how to live broadcasting . The results of this study indicate this technology is very useful in academic and general environment especially in UINSA and Society.